Association between the Frequency of Dining Out and the Risk of Obesity, Diabetes Mellitus, and Dyslipidemia among Korean Adults. Issue 6 (2nd November 2019) - Choi, Mi-Kyeong; Lee, Yeon-Kyung; Heo, Young-Ran; Hyun, Taisun; Lyu, Eun-Soon; Park, Haeryun; Ro, Hee-Kyong; Bae, Yun Jung
ABSTRACT: This study aimed to clarify the association between the frequency of dining out and the risk of obesity, diabetes mellitus, and dyslipidemia among Korean adults. This cross-sectional study surveyed 640 participants aged 20–69 years in Korea. Daily intake of energy, fat, protein, and cholesterol significantly increased as the frequency of dining out increased ( P < .001). Energy derived from carbohydrates significantly decreased with the frequency of dining out, while that derived from fat and protein increased ( P < .001). Among participants who rarely dined out, the fully adjusted odds ratios (ORs) for hyperglycemia were significantly lower at 0.35 (95% CI, 0.16–0.76). Decreased risk of being hyperglycemia among participants who rarely dined out suggests that the frequency of dining out can be related to diabetes risk.